Treatment of Hemophilic Ankle Arthropathy with One-Step Arthroscopic Bone Marrow–Derived Cells Transplantation. (July 2015) - Buda, Roberto; Cavallo, Marco; Castagnini, Francesco; Cenacchi, Annarita; Natali, Simone; Vannini, Francesca; Giannini, Sandro
Objective: Ankle arthropathy is a frequent and invalidating manifestation of hemophilia. Arthrodesis is the gold standard surgical procedure in end-stage disease, with many drawbacks in young patients. Recent literature has shown increase interest in regenerative procedures in hemophilic arthropathy, which may be desirable to delay or even avoid arthrodesis. The aim of this article is to present five cases of osteochondral lesions in ankle hemophilic arthropathy treated with a regenerative procedure: bone marrow–derived cells transplantation (BMDCT). Design: We report five hemophilic patients (four cases with hemophilia type A; one case with hemophilia type B) who have undergone BMDCT treatment, synovectomy, and arthroscopic debridement, with the use of autologous platelet-rich fibrin, to treat osteochondral lesions in hemophilic ankle arthropathy. The patients, included within this retrospective study, were clinically and radiologically evaluated with serial follow-ups, using the American Orthopaedic Foot and Ankle Society (AOFAS) scores, radiographs, and magnetic resonance imaging (MRI). Results: The mean preoperative AOFAS score was 35. After a mean follow-up of 2 years, the mean postoperative AOFAS score was 81, which included three patients returning back to sporting activities. The MRI Mocart score demonstrated signs of regeneration of chondral and bony tissue. No progression of joint degeneration was shown radiographically. Conclusion: BMDCT is a promising regenerative treatment for osteochondral lesions in mild ankle hemophilic arthropathy, which may be useful to delay or even avoid ankle arthrodesis. Nevertheless, longer follow-ups and a larger case series are required.